Sistem Informasi Pengelolaan Dana BOS Berbasis Website Pada SMP Negeri 5 Purwokerto - Antonius Ary Setyawan; Endang Setyawati; Fransiska Bertrik Kristiani (INCODING: Journal of Informatics and Computer Science Engineering, 2021)
The application of Information Technology has now spread almost in all areas including the use of School Operational Fund (BOS) may be all activities of the use of operational grants utilizing information technology. School Operational Aid is a government program that essentially is to provide funding for nonpersonal school operating costs for basic education units as implementers of the 9-year compulsory education program.. A problem that often occurs in the use of school grants is that the current system still has difficulties controlling the operational budget every quarter so that there is still a substantial budget out of the budget set previously in the School Budget Activities Plan (RKAS). With this research, the researcher designed an information system for maniging school-based operational funds using PHP programming language, MySQL database, prototype method. It is hoped that the BOS treasurer in providing information o the use of BOS funds will be more structured, better and faster in preparing quarterly reports, and able to produce accurate and accurate information and reporting. Considering the use of the web as well as direct monitoring of school principals and school commitees in the use of BOS funds so that budget misuse does not occur, so that with this system can provide information more quickly and accurately in managing BOS funds. Website-based BOS fund management information system in SMP Negeri 5 Purwokerto has approved its benefits with the usability variable 97,40%, learnability 98,90%, 100% efficiency, and 97,70% acceptable. Another test results from paired sample T-tests about before and after using the system for presenting financial statements. Variables before and after have a significant value (2 tailed) smaller than 0,05. From these results Ho is rejected and H1 is accepted.